Assessing nicotine dependence using an oral nicotine free-choice paradigm in mice. (October 2019) - Bagdas, Deniz; Diester, Clare M.; Riley, Jason; Carper, Moriah; Alkhlaif, Yasmin; AlOmari, Dana; Alayoubi, Hala; Poklis, Justin L.; Damaj, M. Imad
Abstract: Models to assess the addictive-like properties of nicotine in mice are limited. Therefore, we aimed to characterize and validate an addiction index by using an oral nicotine free-choice paradigm in mice. Adult C57BL/6J, DBA/2J, or genetically modified mice carrying deletions for nicotinic acetylcholine receptor (nAChR) subunits, (n = 8–10/sex/group) were given a choice of water or nicotine (10–960 μg/ml) solution using a two-bottle free-choice (2BC) paradigm. In general, oral nicotine intake and preference were higher in female mice compared to males. Absence of nicotine led to withdrawal, and intermittent access resulted in an escalation in consumption and greater nicotine withdrawal than continuous exposure. Additionally, oral nicotine consumption increased nucleus accumbens tyrosine hydroxylase levels. While β2 and α6 KO mice showed a significant decrease in nicotine intake, deletion of α5 nAChRs increased nicotine consumption at high concentrations. Deletion of the α7 subunit altered the observed sex difference in nicotine consumption, with females consuming less than males. The α4β2 partial agonist varenicline decreased oral nicotine consumption. Although addition of quinine to the nicotine solution lowered nicotine intake, mice primed with nicotine did not lower their intake after quinine addition. Nicotine deprivation followed by re-exposure showed increased nicotine consumption, and DBA/2J mice consumed less nicotine compared to C57BL/6J. We validated the mouse 2BC paradigm to study nicotine's addictive-like properties including nicotine intake, preference, withdrawal, and escalation of nicotine consumption during binge drinking or after reinstatement of a deprivation period. Highlights: Oral nicotine consumption is sex-, strain- and concentration-dependent. β2, α5 and α6 nAChR subunits play a key role in nicotine consumption. Intermittency of nicotine solution leads to an escalation of nicotine consumption. Absence of nicotine results in somatic and affective withdrawal signs.